The effect of gender on the morphology and dimensions of the incisive canal in the Turkish population: CBCT study - Emel Tuğba ATAMAN DURUEL; Onurcem DURUEL (Gazi University, 2022)
Objective: Evaluation of the incisive canal located in the midline and just behind the central incisors before dental implant applications in the anterior maxilla is important for the success of the treatment. The aim of this study was to evaluate the morphology and dimensions of the incisive canal, and to examine the possible effects of gender on these parameters. Materials and Method: Cone beam computed tomography (CBCT) images of 160 randomly selected patients who applied to Hacettepe University Faculty of Dentistry, Periodontology Department for dental implants were included in the study. The height of the incisive canal, the diameter of the incisive foramen, and the morphological type of the incisive canal (cylindrical, banana-like, hourglass-like, funnel-like shape) were evaluated in the CBCT images. For numerical variables, the t-test was used to compare two groups, and the chi-square test was used to examine the relationship between categorical variables. Statistical significance level was accepted as p<0.05. Results: The mean values of incisive canal height and incisive foramen diameter were 10.91 ± 3.44 and 3.48 ± 1.05 mm, respectively. While the cylindrical shape was the most frequent incisive canal configuration, hourglass-like canals were observed to be the least. The height of the incisive canal and the diameter of the incisive foramen were significantly higher in males than females (p<0.05). Conclusion: Gender had no effect on the distribution of the morphological type of the incisive canal. It was found that the sizes of the incisive canal were higher in male subjects.